Calculus: Early Transcendentals 8th Edition

Published by Cengage Learning
ISBN 10: 1285741552
ISBN 13: 978-1-28574-155-0

Chapter 1 - Review - Exercises: 3

Answer

$\frac{f(a+h)-f(a)}{h}=2a+h-2$

Work Step by Step

$\frac{f(a+h)-f(a)}{h}=\frac{(a+h)^2-2(a+h)+3-(a^2-2a+3)}{h}= \frac{a^2+2ah+h^2-2a-2h+3-a^2+2a-3}{h}= \frac{2ah+h^2-2h}{h}=2a+h-2$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.